ANALISIS KEMAMPUAN MENYUSUN RPP KURIKULUM 2013 PADA MAHASISWA PENDIDIKAN KIMIA FKIP UNIVERSITAS TANJUNGPURA - Istiqomah, Fatiyatul; Hairida, Hairida; Muharini, Rini (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractStudents of Chemistry Education FKIP Tanjungpura University have got the learning about making lesson plan based on curriculum 2013. But until now, no report about students? ability to make lesson plan in this study program, so that the analysis was needed to be done. The research purposes were to describe the ability of Chemistry Education?s Students to make a lesson plan based on curriculum 2013 and to describe the difficulties faced. The methode of the research was descriptive with study case involved 64 students of Chemistry Education from semester VI year 2015 Class A, PGMIPA-U and PPAPK as a participant. Cognitive ability test, scoring rubric of lesson plan, and questionnaire, were used to collect data. In addition, interview based on the former instrumen was conducted. The results showed that the ability of Chemistry Education?s Students to make a lesson plan based on Curriculum 2013 in cognitive aspect was still low with the avarege score 50,27 and in psychomotoric aspect was high with the avarege score 80,61. The difficulties faced by students were to make a competence achievement indicator, choose a model, methode and media, design a core activity, and to make an achievement instrument. Keywords: Ability of making Lesson Plan, Student of Chemistry Education, Curriculum 2013